XY chromosome nondisjunction in man is associated with diminished recombination in the pseudoautosomal region. - Hassold, T J (1991)
To assess the possible association between aberrant recombination and XY chromosome nondisjunction, we compared pseudoautosomal region recombination rates in male meiosis resulting in 47,XXY offspring with those resulting in 46,XY and 46,XX offspring. Forty-one paternally derived 47,XXYs and their parents were tested at six polymorphic loci spanning the pseudoautosomal region. We were able to detect crossing-over in only six of 39 cases informative for the telomeric DXYS14/DXYS20 locus. Subsequently, we used the data to generate a genetic linkage map of the pseudoautosomal region and found it to be significantly shorter than the normal male map of the region. From these analyses we conclude that most paternally derived 47,XXYs result from meiosis in which the X and Y chromosomes did not recombine.